2010
DOI: 10.4314/bajopas.v2i1.58479
|View full text |Cite
|
Sign up to set email alerts
|

Study on the phytochemical and invitro antibacterial activity of some spice extracts on some bacteria isolated from meat products

Abstract: The invitro activity of ethanolic and water extracts of some spices on some bacteria isolated from kilishi (a traditional meat snack) was investigated by disc diffusion method. Disc concentrations of 10, 100, 1000, 2000 and 3000μg were used. The result showed that the ethanolic extract of ginger was active against Salmonella at disc concentrations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Ginger extract conferred the highest antimicrobial activity on the product in each of the storage day since products containing ginger consistently has the least microbial load in each of the days. Apart from its noticeable antioxidant activity ginger has been reported to be effective as antimicrobial (Shamsuddeen et al, 2009;Ibrahim et al, 2011). Ginger has been shown to be effective against the growth of both Gram-negative and Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Ginger extract conferred the highest antimicrobial activity on the product in each of the storage day since products containing ginger consistently has the least microbial load in each of the days. Apart from its noticeable antioxidant activity ginger has been reported to be effective as antimicrobial (Shamsuddeen et al, 2009;Ibrahim et al, 2011). Ginger has been shown to be effective against the growth of both Gram-negative and Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…(c) It causes changes in the functions of the normal activity of cell membranes such as electron transfer, nutrient exchange, protein synthesis, nucleic acids and enzymatic activity (4). Similarly, it has been shown that added rosemary and ginger have an inhibitions effect on bacteria (6,30) Table (2) that TBA values of the patties with the added either rosemary or ginger extracts were significantly (p<0.01) lower than control during the entire period of the experiment .Moreover, it was also noticed that the addition of ginger extract is more effective as an antioxidant as compared with the addition of rosemary. Similarly, Formanek et al,(12), Ibrahim et al, (16), and Abu-almaaly (1) reported that ginger extract as antioxidant was effective against TBA formation when incorporated into meat during frozen storage.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the rhizome of the ginger species, (Zinger officinale) is widely used as a spice and food seasoning due to its sweet aroma and pungent taste. It has also been known to have antioxidant activity (20, 33) and is effective as antimicrobial (16,30) due to the presence of gingerol and shogaol (15). Also rosemary have been used as successful antioxidants in vacuum packaged raw ground beef and pork (27) , cooked ground beef (2), and more effective than a combination of BHA/BHT in raw frozen sausage (29), due to its content certain compound rosmanol, rosmariquinone, rosmaridiphenol, carnosol (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…This is called the spice-blending effect . However, Shamsuddeen (2009) reported that individually the extracts of the spices are more active against microorganisms than when they were combined. This finding limits their antibacterial activity in the product, although the sensory properties are found to be amplified.…”
Section: Discussionmentioning
confidence: 99%